S trategies for conservation of historical renderings. Factors and decision criteria - Veiga, M. R. (2011)
The conservation of historical renderings is not a common practice nowadays, since there are many cases of indiscriminate removal and repair with incompatible materials that undermine technical and material history of these building elements. Due to their historical, technical (construction and materials) and aesthetic importance, such renderings present knowledge and technology that should be preserved as cultural heritage. In this sense, the technical intervention adopted must be chosen by taking into account the analysis of collected data about the building, and in particular, about the rendering, stressing the importance of an interdisciplinary approach. In the scope of the consolidation of this interdisciplinary perspective, it is proposed, from an ongoing study, the construction of a set of matrices where a methodology of intervention could be defined based on several concepts and decision criteria.